2018
DOI: 10.1111/flan.12344
|View full text |Cite
|
Sign up to set email alerts
|

Development of derivational morphological awareness in anglophone learners of Spanish: A relational knowledge study

Abstract: This article investigated the development of morphological awareness (MA) across three groups of students of Spanish as a second language (SSL) with different levels of proficiency. Four morphological assessment tasks on relational knowledge were designed in a simultaneous cross‐sectional study that differed in two dimensions: complexity level (low vs. high) and type (detection vs. production). The results demonstrate that MA in Anglophone students of SSL shows an early development but that detection tasks imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Several studies addressed the matter in bilingual children, who are schooled at least partially in their L2, and showed that morphological awareness also helps the development of a L2 (Altman, Goldstein & Armon-Lotem, 2018;D'Angelo et al, 2017;Kieffer & Lesaux, 2008, 2012Kim et al, 2015). Data regarding adult bilinguals, who learned L2 at school with small exposure to L2, are more recent and the role of morphological awareness in L2 is less evident (Jiang & Kuo, 2019;Koda & Miller, 2018;Kraut, 2015;Sánchez-Gutiérrez & Hernández Muñoz, 2018;Wu & Juffs, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies addressed the matter in bilingual children, who are schooled at least partially in their L2, and showed that morphological awareness also helps the development of a L2 (Altman, Goldstein & Armon-Lotem, 2018;D'Angelo et al, 2017;Kieffer & Lesaux, 2008, 2012Kim et al, 2015). Data regarding adult bilinguals, who learned L2 at school with small exposure to L2, are more recent and the role of morphological awareness in L2 is less evident (Jiang & Kuo, 2019;Koda & Miller, 2018;Kraut, 2015;Sánchez-Gutiérrez & Hernández Muñoz, 2018;Wu & Juffs, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…-English L2 morphological awareness in French-speaking participants will increase with their English proficiency (see also Jiang & Kuo, 2019;Kraut, 2015;Sánchez-Gutiérrez & Hernández Muñoz, 2018). -An interaction will exist between proficiency and whether the morphological characteristics are shared with French.…”
Section: Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, morphology plays a beneficial role in reading acquisition (e.g., D'Alessio, Jaichenco, & Deacon & Francis, 2017), vocabulary learning (Sparks & Deacon, 2015), spelling (Sánchez-Gutiérrez, 2013) and reading comprehension in children (Deacon, Kieffer, & Laroche, 2014). Morphology has also been shown to continue to benefit word processing (i.e., word reading and word recognition) in children with dyslexia who have not yet mastered whole-word processing (e.g., Marcolini, Traficante, Zoccolotti, & Burani, 2011;Suárez-Coalla, Martínez-García, & Cuetos, 2017) and it is related to higher levels of linguistic proficiency in learners of second/foreign languages (Sánchez-Gutiérrez & Hernández-Muñoz, 2018). Also, neurological patients with semantic deficits such as those presenting with the semantic variant of primary progressive aphasia show difficulties in the comprehension and production of morphologically complex words (Auclair-Ouellet, Fossard, Houde, Laforce, & Macoir, 2016;Auclair-Ouellet, Fossard, Laforce, Bier, & Macoir, 2017).…”
mentioning
confidence: 99%